The Miami International Evidence-based Guidelines on Minimally Invasive Pancreas Resection. Issue 1 (January 2020) - Asbun, Horacio J.; Moekotte, Alma L.; Vissers, Frederique L.; Kunzler, Filipe; Cipriani, Federica; Alseidi, Adnan; D'Angelica, Michael I.; Balduzzi, Alberto; Bassi, Claudio; Björnsson, Bergthor; Boggi, Ugo; Callery, Mark P.; et al.
Abstract : Objective: The aim of this study was to develop and externally validate the first evidence-based guidelines on minimally invasive pancreas resection (MIPR) before and during the International Evidence-based Guidelines on Minimally Invasive Pancreas Resection (IG-MIPR) meeting in Miami (March 2019). Summary Background Data: MIPR has seen rapid development in the past decade. Promising outcomes have been reported by early adopters from high-volume centers. Subsequently, multicenter series as well as randomized controlled trials were reported; however, guidelines for clinical practice were lacking. Methods: The Scottisch Intercollegiate Guidelines Network (SIGN) methodology was used, incorporating these 4 items: systematic reviews using PubMed, Embase, and Cochrane databases to answer clinical questions, whenever possible in PICO style, the GRADE approach for assessment of the quality of evidence, the Delphi method for establishing consensus on the developed recommendations, and the AGREE-II instrument for the assessment of guideline quality and external validation. The current guidelines are cosponsored by the International Hepato-Pancreato-Biliary Association, the Americas Hepato-Pancreato-Biliary Association, the Asian-Pacific Hepato-Pancreato-Biliary Association, the European-African Hepato-Pancreato-Biliary Association, the European Association for Endoscopic Surgery, Pancreas Club, the Society of American Gastrointestinal and Endoscopic Surgery, the Society for Surgery of the Alimentary Tract, and the Society of Surgical Oncology. Results: After screening 16, 069 titles, 694 studies were reviewed, and 291 were included. The final 28 recommendations covered 6 topics; laparoscopic and robotic distal pancreatectomy, central pancreatectomy, pancreatoduodenectomy, as well as patient selection, training, learning curve, and minimal annual center volume required to obtain optimal outcomes and patient safety. Conclusion: The IG-MIPR using SIGN methodology give guidance to surgeons, hospital administrators, patients, and medical societies on the use and outcome of MIPR as well as the approach to be taken regarding this challenging type of surgery. Abstract : Supplemental Digital Content is available in the text